Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. The role of transformational leadership in enhancing organizational reputation A field study on administrative staff in health affairs in Jeddah Mr. Mohammed Khalid Mohammed Alsulami, Co-Prof. Faisal Ahmed Abed Shuaibi 2. Advertising policies and their role in increasing the market share: An applied study on Saleh Hussain Al Salama Group of Companies, Kingdom of Saudi Arabia Mr. Bandar Abdulraheem Alghamdi 3. The role of the private sector in the development of the economics and services of Hajj and Umrah Mr. Ibrahim Ahamad Hurubi 4. The impact of internal audit quality on fighting corruption in the Qatari public sector Dr. Omer Mahgoub El-Hussaein 5. The Reality of Managing Academic Competencies at Prince Sittam Bin Abdulaziz University Mrs. Hessah Mohammed Alkhonain, Dr. Nora Hamad Almashal 6. Functional combination and its impact on employee productivity Dr. Rayan Adnan Aziz Alrahman 7. The role of lean management in achieving institutional excellence An Empirical Study: Asir Central Hospital in Abha Ms. Neamah Adel AlDoshan